PREVALENSI DAN FAKTOR RISIKO KOKSIDIOSIS (Eimeria sp.) PADA PEDET DI KABUPATEN BOYOLALI - , TITO RIYAN WICAKSANA; , Prof. Dr. drh. Bambang Sumiarto, SU., M.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Coccidiosis (Eimeria sp.) is a parasitic disease that cause a lot of harm to the farmers, because it can lead to decreasing quality and productivity of lifestock. The study aim was to determine the prevalence and risk factor of coccidiosis in calves in Boyolali, Central Java. The sample used in this study were faecal calf with the age of less than one month to one year old. This study used a crosssectional statistical method to measure the association between case of Eimeria infection in calves with various factor that causes coccidiosis (Chi-square) and quantify the strenght of association (Odd ratio). Cluster sampling technique used to collected 338 calf faecal sample from 225 choosen farm. Faecal samples were collected directly from rectum or shortly after defecation and examined using centrifugal flotation method. The positive results for fecal were found Eimeria oocysts in 48.2% (163/338). There were statistically significant difference associations (P<0.05) in prevalence of Eimeria infection among the factor of farm area, age, and type of maintenance calves. The pasture calves have a higher risk (OR=10.2) against Eimeria infection compared to risk factor of age (OR=2.9) and farm area (OR=1.9).